Um olhar sobre práticas pedagógicas que transgridem os estereótipos de gênero na educação infantil na região metropolitana de Belo Horizonte - Lorena Marinho Silva Aguiar (2016)
This thesis is a Masters research and has had as main objective to analyze the pedagogical practices of early childhood education teachers who, embedded in a heteronormative and sexist culture, seek, through their practices, to transgress gender stereotypes. It was also intended to identify, in the pedagogical practices of these professionals, movements/moments of resistance and questions directed to these socially predetermined models and understand, through the vision of these educators, how legislation, educational reforms, interpersonal relationships, living conditions affect the professional performance from a gender perspective. Regarding to the methodological aspect, I have developed a qualitative research and, in order to collect data, I have made observations in the classroom and done semi-structured interviews with early childhood education teachers who teach in Contagem and Belo Horizonte, Brazil. The thesis has analyzed their pedagogical practices reflecting/discussing whether or not these practices transgressed gender stereotypes, demonstrating the importance of such actions to the deconstruction of hegemonic and heteronormative identities. As a result, it presents highly relevant pedagogical practices regarding the transgressions of gender stereotypes. These were practices that took place in the daily activities of teachers; it means that they were not planned for this research. At the end of this research process, I suggest the need for an investment in teacher education in the area of gender and sexuality. I also believe this research may help to (re)think teaching practices towards a non-discriminatory and democratic education.